Epidemiology and Anesthetic Risk in Dogs with Aural Hematoma - Rodrigues, Nhirneyla Marques; Quessada, Ana Maria; Silva, Fabiane Leite da; Silva, Esther Machado de Carvalho e; Neto, João Moreira da Costa; Lima, Wagner Costa (Acta Scientiae Veterinariae, 2016)
Background: Otohematoma or aural hematoma in dogs is blood pooling within the ear cartilage plate, and stems from several causes (ear infections, ectoparasites and others). The formation of hematoma is by vascular injury, causing bleeding, generated by self-injury. This disease occurs especially in dogs of pendulous ears, and the concave surface of the ear is considered as the most frequent. The therapy to correct the lesion can be a clinical procedure; however, surgical drainage is the treatment of choice. This work aims to record the epidemiological aspects related to aural hematoma in dogs, as well as classify such patients as to the physical condition and anesthetic risk. Materials, Methods & Results: Twenty five dogs with aural hematoma submitted to surgical procedure were followed. During the data collection period (seven months), surgery to correct aural hematoma represented 19% of surgeries performed in dogs (total of surgeries: 474). The percentage of canine breeds affected was: mixed breed (64%; 16/25), german shepherd (24%; 6/25), labrador (4%; 1/25), waimaraner (4%; 1/25) and daschund (4%; 1/25). Most occurrences were observed in females aged 3-12 years. Most of the animals showed only one pina affected (96%; 24/25), and 52% (13/25) had hematoma in the right and 44% (11/25) in the left ear. Some of the patients had no hematologic abnormalities (48%; 12/25), but some animals showed normocytic normochromic anemia (36%, 9/25), leukocytosis (8%; 2/25) and thrombocytopenia (8%; 2/25). Among animals, there were only dogs classified as ASA II and ASA III with similar rates (56% and 44% respectively). No deaths were observed among cases analyzed. Discussion: The high prevalence of the disease in mongrel dogs can be explained by the great number of mongrel animals in the service analyzed. Aural hematoma was more frequent in older dogs probably because animals in this age group are more affected by otitis externa, which can predispose them to aural hematoma. Otohematoma was common in animals with pendulous ears, probably because these dogs are more prone to ear diseases than animals with erect ears. Females are more affected, and these data are different to those of other studies, and may be related to changes of the clientele among males and females. Only 4% (1/25) showed bilateral aural hematoma which, actually, is less common. Haematological abnormalities observed may be related to the appearance of aural hematoma, but were unspecific and common to several diseases. Animals classified as ASA II entered in this category for being carriers of mild haematological disorders, especially anemia (36%; 9/25). Dogs classified as ASA III showed signs of moderate systemic disease, and the main suspected disease was ehrlichiosis, which may be associated with aural hematoma. Animals underwent surgical procedure even though being classified as ASA II and III. Such procedure caused no detectable adverse effects and no deaths were recorded. It is expected that mortality is higher in patients classified in a higher grade. The absence of deaths can be related to ASA classification, which was only up to Grade III (moderate systemic disease). Moreover, surgery to drain aural hematoma is considered free of contamination, minimally invasive and without the involvement of important anatomical structures that could systemically compromise patients.